(untitled) (International Journal of Engineering and Computer Science, 2015)
Mobile ad-hoc network is an infrastructure-less network in which the routing operation plays an important role. Due to the infrastructure-less nature of ad-hoc network, it has different issues like MAC layer, routing, security, network survivability etc. One of them is network survivability which needs more concern. It is the ability of a network keeping connected under attacks and failures in the design and performance of wireless ad hoc sensor networks. The large portion of research efforts concentrates on maximizing the network lifetime, where the lifetime of network is evaluated from the time of deployment to the point when one of the nodes has spent its limited power source and becomes in-operational – commonly referred to as first node failure. There is a class of resource consumption attacks called vampire attack which permanently disables the whole network by quickly draining nodes battery power. These types of attacks alter targeted packets by preparing long routes or misguiding the packets. Malicious nodes use false messaging, or alter routing information. This action affects the bandwidth and node battery power. This paper proposes a system that detects and eliminate the vampire attacks by using IDS and thus make the network live.